1975
DOI: 10.1097/00006254-197511000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Successful Pregnancy in Patient on Regular Dialysis

Abstract: made in groups with differing severities of illness or temperatures intergroup comparisons of the means of the logarithmic values were made by Student's unpaired t test. Case 4 was excluded from statistical analyses involving gastrin concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…1 Although the clinical value of blood pressure control has not been demonstrated in all case reports, we observed that, overall, normalizing blood pressure was the common denominator in all successful pregnancies. 3 Our patient was always normotensive and we believe this was the main reason for the favorable outcome. In addition, special attention was given to avoid hypotensive episodes during dialysis.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…1 Although the clinical value of blood pressure control has not been demonstrated in all case reports, we observed that, overall, normalizing blood pressure was the common denominator in all successful pregnancies. 3 Our patient was always normotensive and we believe this was the main reason for the favorable outcome. In addition, special attention was given to avoid hypotensive episodes during dialysis.…”
Section: Discussionmentioning
confidence: 62%
“…Some authors recommend aggressive dialysis to achieve variable target predialysis blood urea nitrogen and creatinine values. 1,3,7 However, our patient received vigorous dialysis only after the 20th week of gestation, by which time organogenesis is completed. This suggests that azotemia may not be the most important factor influencing the outcome of pregnancy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…With the latter dialysis modality, the dialysis‐induced, large reduction in serum osmolality as a result of large decreases in the levels of waste products such as BUN, in the absence of comparable decreases in the “sequestered” amniotic fluid, may lead to movement of water into the amniotic cavity and the development of polyhydramnios in a pregnant dialysis patient. Better adjustment of plasma volume as a result of more frequent dialysis treatment may also help control hypertension, as well as lower the risk of dialysis‐induced hypotension, thus lowering the incidence of fetal distress and premature labor 9,11 , 12 . Serum electrolytes need to be monitored at least weekly to avoid hypokalemia.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with impaired renal function, however, this compensation cannot take place. The increased frequency of dialysis in pregnant patients has led Hou et al 9,11 . to advocate the use of a low‐bicarbonate dialysate (25 mEq/L) to avoid exposing the fetus to unphysiologic serum bicarbonate levels.…”
Section: Discussionmentioning
confidence: 99%